The Influence of Simulation-Based Learning Methods on the Clinical Competence of Midwifery Students - Fathiyati Fathiyati; Hardjito S. Darmojo (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2020)
Clinical competence is an important aspect of midwifery education because it is directly related to students' ability to provide safe, effective, and professional midwifery care. One learning method considered capable of improving students' clinical competence is simulation-based learning. This study aims to explore the effect of simulation-based learning methods on the clinical competence of midwifery students. The study used a qualitative approach with a descriptive phenomenological design. The study participants were 15 midwifery students selected using a purposive sampling technique. Data collection was conducted through in-depth interviews, participant observation, and documentation. Data analysis used thematic analysis through the processes of data reduction, coding, theme identification, and interpretation of meaning. The results showed that simulation-based learning methods had a positive impact on improving the clinical competence of midwifery students. Students experienced improvements in clinical practice skills, critical thinking skills, clinical decision-making, therapeutic communication, and teamwork. In addition, simulation also helped increase students' confidence in facing real-life clinical practice because they gained training experiences that resembled actual health care conditions. However, the study also identified several obstacles to implementing simulations, such as limited laboratory facilities, a limited number of simulation tools, and less than optimal practice time. This study concluded that simulation-based learning methods are effective in improving the clinical competence of midwifery students and can be an innovative learning strategy in modern midwifery education.